A REVIEW OF J. E. SUMERAU'S "PALMETTO ROSE" - Cannell, Chloe (Art/Research International)

(untitled) (University of Alberta, 2021)
J. E. Sumerau’s latest fiction novel Palmetto Rose tells the story of Kid, a bi+, gender fluid twenty-something, living with grief for their romantic partner, alongside their chosen family of LGBTQIA+ friends. This review looks at how Sumerau’s writing presents complex concepts, research, and lived experience for an academic and wider audience.